Hubungan Antara Motivasi Intrinsik Dengan Organizational Citizenship Behavior (OCB) Pada Asisten Mata Kuliah Praktikum Di Universitas Muhammadiyah Surakarta - Apriyanto, Faishal; , Susatyo Yuwono, S.Psi, M.Si, Psi (2016)
ABSTRACT The organization usually believes that we should try the best to gain the superiority than the other members of organization, it causes the members of organization to work more than the well defined description or so called Organizational Citizenship Behavior (OCB). This behavior is definitely expected by the college institution especially for practical work assistant. Intrinsic motivation is one of the principal factors that is decisive in OCB, because the individual has a big pretension to involve themselves in organization activities. The aim of this research is to understand the correlation between intrinsic motivation and OCB, the effective contribution of intrinsic motivation and OCB, the level of Intrinsic Motivation and OCB. The subject of this research is 250 of university student who become practical work assistant of the selected faculties, such as Psychology faculty, School of Teacher Training and Education, Medicines faculty, Techniques faculty and Health faculty. The data collection technique of this research is cluster random sampling. The approximation method of this research is Quantitative using measuring scale of intrinsic motivation and scale of OCB. The data analysis technique of this research is the correlation analysis from Pearson using SPSS 15 for Windows program. By the outcome of data analysis, we can obtain the correlation coefficient 0,885 with sig = 0,000; (p < 0,001) which means there is a significant positive relation between intrinsic motivation and OCB for practical work assistant in Muhammadiyah University of Surakarta. The effective contribution or intrinsic motivation role for OCB is as big as 78, 3 % and another factors influence the rest of it as big as 21, 7 %. The variable of OCB has a mean empiric (RE) as big as 100, 74 that one can say high category. Whereas the variable of intrinsic motivation is known to have a mean empiric (RE) as big as 92, 92 that one can say high category. Keyword: Intrinsic Motivation, Organizational Citizenship Behavior (OCB), Practical Work Assistant